2003
DOI: 10.1128/aem.69.2.796-804.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Initial Reactions during the Cometabolic Oxidation of Methyl tert -Butyl Ether by Propane-Grown Mycobacterium vaccae JOB5

Abstract: The initial reactions in the cometabolic oxidation of the gasoline oxygenate, methyl tert-butyl ether (MTBE), by Mycobacterium vaccae JOB5 have been characterized. Two products, tert-butyl formate (TBF) and tert-butyl alcohol (TBA), rapidly accumulated extracellularly when propane-grown cells were incubated with MTBE. Lower rates of TBF and TBA production from MTBE were also observed with cells grown on 1-or 2-propanol, while neither product was generated from MTBE by cells grown on casein-yeast extract-dextro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
3
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 49 publications
8
108
3
3
Order By: Relevance
“…Propane was a good inducer of TBA degradation activity in M. vaccae JOB5 (Fig. 3), as previously determined by Smith et al (2003).…”
Section: Expression Of M Austroafricanum Ifp 2012 Alkb Genesupporting
confidence: 66%
See 1 more Smart Citation
“…Propane was a good inducer of TBA degradation activity in M. vaccae JOB5 (Fig. 3), as previously determined by Smith et al (2003).…”
Section: Expression Of M Austroafricanum Ifp 2012 Alkb Genesupporting
confidence: 66%
“…Several grampositive microorganisms belonging to the Nocardia-Corynebacterium-Mycobacterium-Rhodococcus complex showed degradation capacity towards TBA. Among them, Mycobacterium vaccae JOB5, isolated for its ability to grow on 2-methylbutane (Ooyama and Foster 1965) oxidised MTBE and also TBA after growth on propane (Hyman et al 1998;Johnson et al 2004;Smith et al 2003;Steffan et al 1997), hexane or 2-methylbutane (Hyman and O'Reilly 1999). Smith et al (2003) showed at a physiological level that a propane-induced monooxygenase was responsible for both MTBE and TBA oxidation in this strain.…”
Section: Introductionmentioning
confidence: 99%
“…A mixed culture may be more suitable for treatment options than pure culture (Pruden et al, 2001). It could be the existence of many rea- (Francois et al, 2003;Smith et al, 2003;Ferreira et al, 2006). However, TBF was not detected in our study.…”
Section: Isolation Of Mtbe-degrading Bacteria From the Gasoline Contacontrasting
confidence: 64%
“…We recently detected 2-methyl 1,2-propanediol (2-M1,2-PD) as the product of TBA oxidation in M. austroafricanum IFP 2012and IFP 2015(Lopes Ferreira et al, 2005, and demonstrated its transformation to 2-hydroxyisobutyric acid (HIBA) in resting-cell experiments. 2-Methyl 1,2-propanediol (2-M1,2-PD) has been reported by Steffan et al (1997), using propane-oxidizing bacteria able to degrade MTBE by cometabolism, and by Smith et al (2003), using Mycobacterium vaccae JOB5 as the product of TBA degradation.…”
Section: Introductionmentioning
confidence: 99%